2022
DOI: 10.7759/cureus.24086
|View full text |Cite
|
Sign up to set email alerts
|

A Tooth Decaying in the Appendix: An Unusual Cause of Appendicitis

Abstract: Appendicitis is a very common indication for surgery, although in recent years uncomplicated cases have often been managed with antibiotics. In this case, we discuss a patient who presented to the emergency department with a case of seemingly uncomplicated acute appendicitis. Physical exam, history, and imaging indicated that this was due to an ingested foreign body, specifically a dental crown, that had impacted the appendix. In cases of ingested foreign bodies, antibiotics are not an appropriate treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The results obtained by Collins et al reported that out of 71,000 appendectomies, 51.8% were caused by obstruction, of which most of them were parasitic worms or faecoliths and only 5.5% of them were considered unusual foreign bodies [11,29]. The ingestion of foreign bodies generally does not cause gastrointestinal complications, such as acute appendicitis, and it can pass within a week with less than a 1% rate of complications [27]. Symptom onset and the entry of a foreign body into the appendix are often dependent on the size and shape of an object and the anatomical position of the appendix [21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results obtained by Collins et al reported that out of 71,000 appendectomies, 51.8% were caused by obstruction, of which most of them were parasitic worms or faecoliths and only 5.5% of them were considered unusual foreign bodies [11,29]. The ingestion of foreign bodies generally does not cause gastrointestinal complications, such as acute appendicitis, and it can pass within a week with less than a 1% rate of complications [27]. Symptom onset and the entry of a foreign body into the appendix are often dependent on the size and shape of an object and the anatomical position of the appendix [21].…”
Section: Discussionmentioning
confidence: 99%
“…Foreign bodies as a possible cause of acute appendicitis have been described in several recent studies (most commonly part of bone or toothpick). Other less common foreign bodies such as earrings, needles, and dental objects have been described [23,24,27,[30][31][32]. A recent study describes how a detailed history revealed that the patient had swallowed a dental crown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations